Systematic identification and functional characterization of the CFEM proteins in fishscale bamboo rhombic-spot pathogen Neostagonosporella sichuanensis - Fang Liang; Fang Liang; Lijuan Liu; Lijuan Liu; Chengsong Li; Chengsong Li; Yinggao Liu; Yinggao Liu; Shan Han; Shan Han; Hua Yang; Hua Yang; et al. (Frontiers in Plant Science, 2024)
Fungal effectors play a crucial role in the interaction between pathogenic fungi and their hosts. These interactions directly influence the invasion and spread of pathogens, and the development of diseases. Common in fungal extracellular membrane (CFEM) effectors are closely associated with the pathogenicity, cell wall stability, and pathogenic processes of pathogenic fungi. The aim of this study was to investigate the role of CFEM proteins in Neostagonosporella sichuanensis in pathogen-host interactions. We retrieved 19 proteins containing CFEM structural domains from the genome of N. sichuanensis. By systematic analysis, five NsCFEM proteins had signal peptides but lacked transmembrane structural domains, and thus were considered as potential effectors. Among them, NsCFEM1 and NsCFEM2 were successfully cloned and their functions were further investigated. The validation results show that NsCFEM1 was localized in the cell membrane and nucleus, whereas NsCFEM2 was exclusively observed in the cell membrane. Both were identified as secreted proteins. Additionally, NsCFEM1 inhibited Bax-induced programmed cell death in Nicotiana benthamiana, whereas NsCFEM2 did not induce or inhibit this response. NsCFEM1 was implicated as a virulence factor that contributes to fungal growth, development, stress response, and pathogenicity. NsCFEM2 was implicated in maintenance of cell wall stability. This study lays a foundation for elucidating the role of CFEM proteins in the pathogen of fishscale bamboo rhombic-spot caused by N. sichuanensis. In particular, the functional studies of NsCFEM1 and NsCFEM2 revealed their potential roles in the interaction between N. sichuanensis and the host Phyllostachys heteroclada.